2013
DOI: 10.1099/jmm.0.047803-0
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite typing of Aspergillus flavus from clinical and environmental avian isolates

Abstract: Aspergillosis is one of the most common causes of death in captive birds. Aspergillus fumigatus accounts for approximately 95 % of aspergillosis cases and Aspergillus flavus is the second most frequent organism associated with avian infections. In the present study, the fungi were grown from avian clinical samples (post-mortem lung material) and environmental samples (eggs, food and litter). Microsatellite markers were used to type seven clinical avian isolates and 22 environmental isolates of A. flavus. A. fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The isolates were collected from different patients, from separate regions of Iran (Table 1), and were collected over an 8-year period. Similarly, the high genetic diversity in A. flavus was observed in clinical strains originating from humans (21) and animals (43). Furthermore, in a previous study, we also showed that clinical and environmental A. fumigatus strains from Iran clustered apart from each other (44).…”
Section: Discussionmentioning
confidence: 88%
“…The isolates were collected from different patients, from separate regions of Iran (Table 1), and were collected over an 8-year period. Similarly, the high genetic diversity in A. flavus was observed in clinical strains originating from humans (21) and animals (43). Furthermore, in a previous study, we also showed that clinical and environmental A. fumigatus strains from Iran clustered apart from each other (44).…”
Section: Discussionmentioning
confidence: 88%
“…For veterinary medicine, Hadrich et al described identical genotypes between avian isolates recovered from lung biopsy specimens and the environment of the birds using VNTR markers (83). The same authors also reported a high genetic diversity between human isolates and environmental and avian isolates (84), which is different from what was reported for A. fumigatus, where differences between the genotypes of avian and human isolates were not detected using STR markers (47).…”
Section: Aspergillus Flavusmentioning
confidence: 95%
“…Sequences of the primer pairs designed for the microsatellite markers AFLA1, AFLA3, AFLA7, AFPM3, AFPM4, and AFPM7 are shown in Table . The PCR mixtures of 20 μl volume contained 10× DreamTaq Buffer (with 1.5 mM MgCl 2 ) (Thermo Scientific), 0.02 mM dNTPs, 4–4 pmol of forward and reverse primers, 10–100 ng of total DNA, 1 U DreamTaq DNA Polymerase (Thermo Scientific) and nuclease free water.…”
Section: Methodsmentioning
confidence: 99%